Complexity of stand structures in two mixed mountain old-growth forests and adjacent managed forests in Bosnia and Herzegovina - Keren, Srdjan (visokošolska dela, 2015)
This study was conducted in Dinaric mixed mountain old-growth (OG) forests Janj and Lom and adjacent managed stands on the same site (Piceo-Abieti-Fagetum illyricum), which were managed with a selection (plenter) system for more than a century. The following attributes were examined: light climate, ground vegetation, regeneration, tree density, dbh distribution shapes, tree species composition, mean diameter, basal area (BA), growing stock (GS) and coarse woody debris (CWD). As expected, taller and larger trees, higher BA, higher share of senescent phase and more CWD were found in OG forests. Regeneration process in OG forests was characterized by lower levels and variability of light, lover ground vegetation coverage and vascular plant diversity, and the species composition was more dominated by beech. Beech seedling density indicated positive relation to beech BA, while all regeneration stages of fir showed negative relation with fir BA. Beech was significantly more represented in OG forests also in the middlestory. Dbh distributions in both managed and OG forests had shapes that indicate a demographic equilibrium, despite high values of GS. Most frequent species specific shapes indicated demographic stability or even progression of beech, and imbalance or regression of conifers. Despite significant shares of spruce and fir in the upperstory, their regeneration and small trees were given low chances to replace mature trees in OG forests in the near future. Similarly to the natural disturbance pattern in OG forests Janj and Lom, single tree selection in managed forests performed only slightly better regarding recruitment of spruce and maple into the stand middlestory. The long-term comparison of OG forest structure indicated decline of conifers (especially spruce). However, comparison of recent data in managed and OG forests indicated that silvicultural activities may hold back long-term conifer decline since managed forests exhibited greater compositional stability.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; mešani gozdovi; jelovo-bukovi gozdovi; pragozd; gospodarski gozd; prebiralno gospodarstvo; gozdni sestoji; strukturne spremembe; bukev; jelka; smreka; disertacije